PET imaging of serotoninergic neurotransmission with [(11)C]DASB and [(18)F]altanserin after focal cerebral ischemia in rats - Martín, Abraham (Nature Publishing Group, 2013)
The use of selective serotonin reuptake inhibitors has shown functional improvement after stroke. Despite this, the role of serotoninergic neurotransmission after cerebral ischemia evolution and its involvement in functional recovery processes are still largely unknown. For this purpose, we performed in parallel in vivo magnetic resonance imaging and positron emission tomography (PET) with [(11)C]DASB and [(18)F]altanserin at 1, 3, 7, 14, 21, and 28 days after middle cerebral artery occlusion (MCAO) in rats. In the ischemic territory, PET with [(11)C]DASB and [(18)F]altanserin showed a dramatic decline in serotonin transporter (SERT) and 5-HT(2A) binding potential in the cortex and striatum after cerebral ischemia. Interestingly, a slight increase in [(11)C]DASB binding was observed from days 7 to 21 followed by the uppermost binding at day 28 in the ipsilateral midbrain. In contrast, no changes were observed in the contralateral hemisphere by using both radiotracers. Likewise, both functional and behavior testing showed major impaired outcome at day 1 after ischemia onset followed by a recovery of the sensorimotor function and dexterity from day 21 to day 28 after cerebral ischemia. Taken together, these results might evidence that SERT changes in the midbrain could have a key role in the functional recovery process after cerebral ischemia.